A review on glassy polymeric membranes for gas separation - Farnam, M. (Trans Tech Publications Ltd, 2014)
Polymeric membranes are widely used for gas separation purposes but their performance is restricted by the upper bound trade-off discovered by Robeson in 1991. The polymeric membrane can be glassy, rubbery or a blend of these two polymers. This review paper discusses the properties of glassy polymer membranes and their performance in gas separation. The area of improvement for glassy membrane with development of mixed matrix membrane is also highlighted. Â© 2014 Trans Tech Publications, Switzerland.